Analisis Penerapan Konsep 5R (Ringkas, Rapi, Resik, Rawat, Rajin) Dalam Pencegahan Penyakit Akibat Kerja Di Unit Filing RSUD Dr. M. Ashari Pemalang - Eni Mahawati; Dewi Ernita (Dian Nuswantoro Semarang, 2020)
Objective: The 5R Method is consists of several stages to get an efficient and effective action in each activity. Based on the results of the 5R implementation survey at the hospital, it was obtained that 5R can support the maintenance of medical records in filing space. The implementation of the 5R method can support work-related disease prevention. The purpose of this study is to describe the application of the concept of 5R in filing space to prevent occupational diseases. Method: It was a descriptive study that uses collecting data methods through observation and interview. The subjects of the study were the head of medical records and eight filing officers. Result: The results showed that there was some condition found such as lack of storage shelves, absence of temperature gauges, lighting and humidity, the absence of an expedition book used to facilitate medical records lending, and retention of outpatients. Sweeping is done to find the lost medical records during service. Conclusion: It was concluded that were the application of 5R in the filing section has not been done thoroughly. The officers do not understand the maintenance of medical records. medical records maintenance and job description for the maintenance do not exist yet. Suggestions: It is suggested that the hospital should increase the socialization to filing officers to implement the 5R method at work, using personal protective equipment and retention for each periodic. It is also suggested to add shelf capacity for storage, providing PPE with masks and gloves as well as tools for temperature and humidity gauges for medical records maintenanceKeywords: Filing, 5R, Medical Records, Occupational, DiseaseLiterature: 9 (2000-2019)